2019
DOI: 10.7196/samj.2019.v109i9.13730
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of isoniazid resistance-conferring mutations associated with multidrug-resistant tuberculosis in Free State Province, South Africa

Abstract: Background. Multidrug-and extensively drug-resistant tuberculosis (MDR-TB and XDR-TB) threaten local and global control of the disease. The molecular line-probe assay (LPA) provides rapid diagnosis and early management of MDR-TB. The LPA detects mutations of katG and inhA genes associated with isoniazid (INH) resistance in Mycobacterium tuberculosis isolates. The katG and inhA genes are associated with high-and low-level INH resistance, respectively, as well as cross-resistance to ethionamide in the case of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
4
23
0
1
Order By: Relevance
“…Tuberculosis (TB) is among the primary health problems, 1,2 particularly in lowincome countries, and is considered as the leading cause of death from a single infectious disease ranking above HIV/AIDS. [3][4][5][6][7][8][9] Worldwide, an estimated 10.0 million people felt ill with an estimated 1.4 million deaths in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis (TB) is among the primary health problems, 1,2 particularly in lowincome countries, and is considered as the leading cause of death from a single infectious disease ranking above HIV/AIDS. [3][4][5][6][7][8][9] Worldwide, an estimated 10.0 million people felt ill with an estimated 1.4 million deaths in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…resistant MTB strains that are often resistant even to other drugs (5,21). Furthermore, studies have indicated a high prevalence of MDR-MTB carrying this mutation of katG 315 (AGC > ACC) from some high TB burden countries such as Bangladesh (80%) (22), Russian Federation (93%) (23), South Africa (87%) (24), and Zambia (91%) (25).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Isoniazid resistance in patients with rifampicin resistant was uncommon, accounting for about 29% compared to over 64% in South Africa [ 48 ] and 78% in China [ 49 ]. In the present study, isoniazid monoresistance was categorised from direct sputum samples which was negative in a large number of patients [ 30 ], as compared to MTC isolates in two studies [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%